Satisfaction Levels of Ambulatory Patients with the Quality of Nursing Care: Validation and Application of the Patient Satisfaction with Nursing Care Quality Questionnaire in Albania - Sonila Qirko; Vasilika Prifti; Emirjona Kicaj; Rudina Çerçizaj; Liliana Marcela Rogozea (Nursing Reports)
Background: In the last decades, there has been a growing demand for outpatient services; understanding the factors influencing patient satisfaction is critical for improving healthcare quality. Objectives: This study evaluates patient satisfaction with nursing care and examines how satisfaction varies based on socio-demographic factors in ambulatory settings across five healthcare centers in the municipality of Vlora, Albania. Methods: In this cross-sectional study, a total of 246 patients were surveyed using the Patient Satisfaction with Nursing Care Quality Questionnaire (PSNCQQ), adapted for outpatient contexts, after assessing its validity and reliability. The mean age of the sample was 63.9 ± 13.1 years old with a range of 21 to 94 years, and 47.2% were aged between 50 and 69 years. Results: The results indicate that the overall satisfaction level was fair, with a mean PSNCQQ score of 2.55 on a five-point scale. Socio-demographic factors, such as age, gender, education, and socio-economic status, significantly impacted patient satisfaction. Younger patients (aged 20–49), females, and those with a higher education and socio-economic status reported higher satisfaction. Medical history also played a role, with patients attending general check-ups showing greater satisfaction compared to those with chronic conditions. Older patients tend to report a lower level of satisfaction with the care provided compared to younger patients. Conclusions: Communication and nurse–patient interactions emerged as key areas for improvement, particularly in outpatient settings where care is episodic. These findings suggest that personalized care, improved communication, and greater attention to socio-demographic and medical factors can enhance patient satisfaction in ambulatory care settings.